Postmodern Transformations in Religious Organization and Ritual Transmission: The Case of Hubyar Ocak (Journal of Alevism-Bektashism Studies, 2025)
Alevi ocak structures developed historically within social contexts characterized by the absence of centralized authority (interregnum) or by the limited reach of state power, evolving in accordance with the internal dynamics of the belief system. As constituent elements of the broader Alevi social structure, these ocaks, which display a relatively autonomous form of organization, may be conceptualized as congregation-based substructures (congregations). Although they do not pursue an explicit missionary agenda, these formations have provided mechanisms for maintaining internal stability and social order, and have existed in Anatolia since at least the thirteenth century. Through their regionally bounded and inward-oriented character, ocaks have managed to protect themselves against external pressures and hostilities from other religious traditions, thereby sustaining their communities over time. This organizational model, which proved stable and effective under medieval conditions and also embodied a form of governance parallel to central authority, has increasingly lost its viability under post-modern conditions. Rapid industrialization and the ensuing waves of mass migration dissolved the geographical and social isolation of Alevi communities, a process that simultaneously initiated the erosion of ocak structures. As Alevis became integrated into new social environments, they were increasingly compelled to distance themselves from traditional institutions and belief-based frameworks. Migration disrupted established patterns of social organization, leading individuals to lose familiar social positions and, consequently, their institutional ties to ocaks. The weakening of these traditional affiliations prompted new forms of social and cultural searching within urbanized contexts, giving rise to alternative organizational structures. Cultural associations and political unions offering secular modes of belonging emerged as prominent options in these new environments. Developments over the past fifty years have thus produced profound transformations in Alevi religious affiliations and practices. Within this broader context, the present study offers an ethnographic observation of these transformations through the specific case of the Hubyar Ocak.